Business Investment in the OECD Economies Recent Performance and some Implications for Policy - Ford, Robert (OECD Economics Department Working Papers, 1990)
Investment growth in the OECD area has been higher in the second half of the 1980s than in the 1970s. However, the ratio of net investment to GDP has remained low by past cyclical standards. This paper first reviews the evolution of business-sector fixed investment and addresses measurement issues related to computers and intangible investment. It then examines the determinants of investment and the extent to which governments can and should influence capital formation. Time-series properties of investment, output and the cost of capital do not appear to be consistent with well-established theories of investment. The best predictor of investment is found to be its own past history. Therefore, although higher investment could be beneficial to future consumption and economic growth, the effectiveness of policies to raise investment via the cost of capital is largely uncertain ...